Loans, link and leadership: Political change and borrower discouragement in connected firms - Jérémie Bertrand; Florian Léon; Caroline Perrin (Fondation pour les études et recherches sur le développement international (FERDI), 2025)
This paper examines how political leaders change moderates the impact of corporate political activity (CPA) on borrower discouragement, using a global dataset of 24,167 firms. While CPA generally reduces discouragement, its effectiveness is significantly diminished during political transitions, as the "know-who" channel becomes unreliable.
Keywords: G21; K38; 330; banking; political connection; borrower discouragement